The Integration of Socio-Cultural Aspects in the English Textbooks entitled English in Mind - Muchamad Saepudin; Januarius Mujiyanto; Suwandi Suwandi (English Education Journal, 2022)
Language and sociocultural are inseparable and bound to each other. Language is the expression of cultural reality, the embodiment of cultural reality, and the symbols of cultural reality. The inseparability of language and culture has led researchers to investigate English language teaching taught in various cultural contexts. This study qualitative approach, in which the data were taken from an English textbook entitled English In Mind published by the Ministry of Education and Culture. The data were gathered by classifying the six sociocultural aspects (nomenclature, address terms, cultural information, cultural sites, sociocultural tradition, etiquette) and analyzed using the theory of sociolinguistics. The finding of this research, After Analyzing fourteen chapters English textbooks observed in this study show "reality", Which reflects the reality of the use of the original language and is in accordance with the sociocultural values of the native speakers. In order to achieve balance, A good textbook should be balanced included some local stories from the background culture of the Indonesian students, as they should be familiar with the story or legend from their own background culture.